Tantangan Kelembagaan Pengendalian Kebakaran Hutan dan Lahan pada Tingkat Tapak - Irfan Kemal Putra; Bambang Hero Saharjo; Basuki Wasis (Jurnal Ilmu Pertanian Indonesia, 2019)
Continuous forest and land fires in Indonesia require multi-stakeholder concerns. Further, focal point should be on the grass root actors, since they are the closest to the fires, in term of location; the understand the most about the site situations, and could be the first responders to the fire events. Those actors, also could play a role as, either protagonists or antagonists, in the fire management program, depend on their situations. Based on the above narration, this research aimed to understand roles and challenges faced by those actors at the site level. This research was conducted in August-December 2017 in three villages, in Siak District, Riau is Village Penyengat, Sungai Rawa, and Rawa Mekar Jaya. The choice of location was based on comparable different fire frequencies occured among those three villages respectively the most, moderately, and the least frequent. The method utilized in this research was actor analysis. The data were collected from primary (interviews) and secondary sources (literatures). The analysis results showed that there were too many key players, influencing actors with negative roles, and actors with improper roles in the fire management activities. De-concentrating the influences of the Central Government and MoEF, as well as derivative legislations to legalize the roles of both the National Agency for Disaster Countermeasures (NADC-BNPB) and Army, to be involved in the fire management activities are also needed to solve the problems.